When the Watchdog Neither Barks Nor Bites: Communication as a Power Resource in Media Policy and Regulation. Issue 3 (16th April 2018) - Ali, Christopher; Puppis, Manuel
Abstract: Communication in policymaking and regulation has been of interest to political scientists for the last 15 years. Lamentably, the conceptualization and analysis of communication in media policymaking and regulation has yet to garner much attention from media policy scholars. Drawing on theories of power and new institutionalism, we address this paucity by introducing a theoretical and methodological approach that centers on the intersection of communication and power in media policymaking. Such a framework is particularly required for media policy studies, since media companies not only represent the regulated parties, but also control the avenues of policy communication. This tremendous amount of power raises normative concerns for bias, silence, and capture of the policymaking agenda.